Multilingualism in incarnational ministry: A quest to reach the neglected - Kabongo, Kasebwe T. L. (HTS teologiese studies, 2022)
Language is a critical tool for communication. This article uses the autoethnographic methodology to describe the author’s experience of language acquisition, which has influenced his understanding of multilingualism in incarnational ministry. He belongs to a missional order, InnerCHANGE, that uses an incarnational approach to ministry. InnerCHANGE understands incarnational ministry as a mission to meaningfully identify with people its members live among. InnerCHANGE’s membership is of diverse backgrounds culturally. Multilingualism within the order and in ministry contexts in a way that makes communication smooth is still an ideal rather than a reality. This article asks how multilingualism could positively contribute to InnerCHANGE’s quest for a meaningful incarnational approach. It found out that multilingualism could be a tangible act of equity and justice. It could also be a way to affirm diversity in a world that is constantly on a quest for a lingua franca, a contradiction to the event of Pentecost found in Acts 2. Finally, it could be an act of solidarity towards the valorisation of languages that some people see as inferior. It concludes by stressing that black Africans should be at the forefront of valorising their native languages in proudly using them and producing knowledge that could be shared with fellow Africans and non-Africans.Contribution: This article intends to contribute to the ongoing debate on the relation of the gospel to culture. Its focus is on language, which is one of the components of a culture.